2011
DOI: 10.1186/1742-4682-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of developing embryo using scale-invariant approach

Abstract: BackgroundSelf-organization is a fundamental feature of living organisms at all hierarchical levels from molecule to organ. It has also been documented in developing embryos.MethodsIn this study, a scale-invariant power law (SIPL) method has been used to study self-organization in developing embryos. The SIPL coefficient was calculated using a centro-axial skew symmetrical matrix (CSSM) generated by entering the components of the Cartesian coordinates; for each component, one CSSM was generated. A basic square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The fractal concept has improved our understanding of many physiological phenomena, for instance, metabolic rate, intracellular bio-energetic dynamics, drug clearance, population genetics, tissue organization and tumor growth. Fractality describes very well the complexity of macroscopic and microscopic anatomic structures and reveals the design principles of organisms [2–67] .…”
Section: Fractality: a General Concept In Biology And Medicinementioning
confidence: 99%
“…The fractal concept has improved our understanding of many physiological phenomena, for instance, metabolic rate, intracellular bio-energetic dynamics, drug clearance, population genetics, tissue organization and tumor growth. Fractality describes very well the complexity of macroscopic and microscopic anatomic structures and reveals the design principles of organisms [2–67] .…”
Section: Fractality: a General Concept In Biology And Medicinementioning
confidence: 99%
“…In nematodes, differentiation trees allow us to relate the binary, mostly asymmetric cell divisions to the broader context of embryonic tissue differentiation. Alternative methods include meta-Boolean models [14], complex networks [10], algorithmic complexity [15], and scale-invariant power laws [16]. One method that relies upon simply reorganizing the lineage tree by the occurrence of differentiation waves is called differentiation tree analysis [11].…”
Section: Analysis Of Developmentmentioning
confidence: 99%
“…interactions, plots as a descending straight line). Several authors have therefore suggested that self-organization in development might be identified by seeking power-law topologies (Kurakin, 2005;Tiraihi et al 2011). Some features of systems known, through experiment, to self-organize do show power-law behaviour: imaging the anatomy of a branching epithelial or vascular tree using voxels of a range of dimensions, assessing the fraction of voxels containing at least some of the tree in each case, and log-plotting the occupancy vs. voxel size yields a power-law line, at least until the voxels become smaller than the smallest tubules (see Fig.…”
Section: Identifying Adaptive Self-organizationmentioning
confidence: 99%